Rancang Bangun Aplikasi Point Of Sales Menggunakan Framework Codeigniter - Sibagariang, Swono; Sinaga, Matheus Eleazar Pratama (Universitas Sari Mutiara Indonesia Medan, 2023)
Rapid technological advances have revolutionized various industries, including the retail sector, especially in the restaurant food category. One of the important developments in this operation is the emergence of a website-based Point of Sale (POS) application. This application utilizes web technology to providse an efficient and easy-to-use solution for managing sales transactions. The main goal is to understand the key features, benefits and challenges associated with this kind of application. The presence of the POS application helps overcome problems associated with manual sales systems, such as errors in recording transactions and the difficulty of monitoring finances. Therefore, this research has succeeded in creating a website-based Point Of Sale application using the prototype method in its development. The POS application uses the Codeigniter framework and MySQL as the database. The application built can help manage master data, transaction data, income and expense report data more easily and quickly. This application has been tested using black box testing. The testing process involved a diverse set of usage scenarios, including food ordering, order management, payment processing, and financial reports, print and print which produced results that matched their functionality.